Dimensão ética do cuidado de si : uma análise voltada aos ambientes competitivos de trabalho a partir das contribuições de Sêneca - Soave, Cláudia (My University, 2014)
This dissertation introduces the ethical sense of self-care focused to the competitive work environments, from the works of Seneca, entitled From tranquility of the Soul, The brevity of life, The happy life and Letters to Lucilio, having as a theory support, the interpretations made by Michel Foucault, in the book The Hermeneutics of the Subject. The study of the mentioned works of Seneca allows to demonstrate their interrelations with self-care and with care of others as well as with the meaning of self-care in the unfailing context of this philosopher. Faced with the question of what is the meaning of self-care in competitive work environments, which can not be restricted only to the extention of physical space, but extend to the dimension of the individual's life, intended to consider the sense of self-care, by the ethical look of Seneca and relate it to competitive work environments. Through analysis of Seneca’s theory and understanding of the competitive environments' formation, supported in the Herbert Marcuse's work, The ideology of one-dimensional society and in the works of Foucault, Monitor and Punish and Words and Things, you can reflect if the self-care and the competition are a paradox for the man who does his job, to guarantee his sustenance or look for higher performance's levels and personnel achievement.
Esta dissertação apresenta o sentido ético do cuidado de si voltado aos ambientes competitivos de trabalho, a partir das obras de Sêneca, intituladas Da tranquilidade da alma, A brevidade da vida, A vida feliz e Cartas a Lucílio, tendo como apoio teórico as interpretações feitas por Michel Foucault, no livro A hermenêutica do sujeito. O estudo das referidas obras de Sêneca permite demonstrar suas inter-relações com o cuidado de si e com o cuidado do outro, bem como, com o significado do cuidado de si, no contexto estoico desse filósofo. Diante da questão sobre qual o sentido do cuidado de si em ambientes competitivos de trabalho, os quais podem não se limitar apenas à extensão do espaço físico, mas se estender à dimensão da vida do indivíduo, examina-se o sentido de cuidado de si, pelo olhar ético de Sêneca, e se o relaciona aos ambientes competitivos de trabalho. Por meio da análise da teoria de Sêneca e do entendimento sobre a constituição dos ambientes competitivos, amparados na obra de Herbert Marcuse, A ideologia da sociedade unidimensional, e nas obras de Foucault, Microfísica do poder, Vigiar e punir e As palavras e as coisas, é possível refletir se o cuidado de si e a competição são um paradoxo para o homem que exerce seu trabalho, seja para garantir seu sustento ou para buscar níveis mais elevados de desempenho e realização pessoal.
Keywords: Ética profissional; Trabalho; Seneca, Lucio Anneo, ca. 4 a.C.-65 d.C.; Foucault, Michel, 1926-1984; Marcuse, Herbert, 1898-1979; Professional ethics; Work